A Simple High-performance Liquid Chromatography Coupled to Fluorescence Detection Method using Column-switching Technique for Measuring Urinary 1-hydroxypyrene from Environmental Exposure - Kunrunya Sutan (Science Faculty of Chiang Mai University, 2019)
A method for determination of urinary 1-hydroxypyrene (1-OHP) was developed using HPLC-FLD with a column-switching system. 1-OHP in urine samples was extracted by b-glucuronidase hydrolysis, followed by C18 SPE with optimized conditions. LOD and LOQ were 0.01 and 0.03 ng/mL, respectively; this was sensitive enough to determine urinary 1-OHP in low-dose exposure. The precision and accuracy of four concentrations (0.06, 2.0, 8.0 and 25 ng/mL) were tested. The intra- and inter-batch precisions were between 1.82-4.22 and 5.01-15.8 %RSD, respectively, while accuracies were between 92.8-117% recoveries, which were in the acceptable range. This method was applied in 130 school children living in a seasonal forest-fire burning area in Northern Thailand. Urinary 1-OHP was detected in all urine samples at concentrations of 1.35±2.26 mmol/mol creatinine, and a range of 0.03-16.0 mmol/mol creatinine. The developed method offers a potential application to determine urinary 1-OHP levels from environmentally low exposure.